Prebiotic Peptide Synthesis and Spontaneous Amyloid Formation Inside a Proto‐Cellular Compartment. Issue 10 (21st January 2021) - Kwiatkowski, Witek; Bomba, Radoslaw; Afanasyev, Pavel; Boehringer, Daniel; Riek, Roland; Greenwald, Jason
Abstract: Cellular life requires a high degree of molecular complexity and self‐organization, some of which must have originated in a prebiotic context. Here, we demonstrate how both of these features can emerge in a plausibly prebiotic system. We found that chemical gradients in simple mixtures of activated amino acids and fatty acids can lead to the formation of amyloid‐like peptide fibrils that are localized inside of a proto‐cellular compartment. In this process, the fatty acid or lipid vesicles act both as a filter, allowing the selective passage of activated amino acids, and as a barrier, blocking the diffusion of the amyloidogenic peptides that form spontaneously inside the vesicles. This synergy between two distinct building blocks of life induces a significant increase in molecular complexity and spatial order thereby providing a route for the early molecular evolution that could give rise to a living cell. Abstract : Self‐organization in a system of fatty acids and activated amino acids leads to vesicle‐encapsulated amyloids. The fatty‐acid vesicles act both as a filter, allowing the selective passage of activated amino acids, and as a barrier, blocking the diffusion of the amyloidogenic peptides that form spontaneously inside the vesicles. Hence, a simple mixture of prebiotically plausible starting materials leads to organizationally complex structures.